Neoglacial climate anomalies and the Harappan metamorphosis - L. Giosan; W. D. Orsi; W. D. Orsi; M. Coolen; C. Wuchter; A. G. Dunlea; K. Thirumalai; S. E. Munoz; P. D. Clift; J. P. Donnelly; V. Galy; D. Q. Fuller (Climate of the Past, 2018)
Climate exerted constraints on the growth and decline of past human societies but our knowledge of temporal and spatial climatic patterns is often too restricted to address causal connections. At a global scale, the inter-hemispheric thermal balance provides an emergent framework for understanding regional Holocene climate variability. As the thermal balance adjusted to gradual changes in the seasonality of insolation, the Intertropical Convergence Zone migrated southward accompanied by a weakening of the Indian summer monsoon. Superimposed on this trend, anomalies such as the Little Ice Age point to asymmetric changes in the extratropics of either hemisphere. Here we present a reconstruction of the Indian winter monsoon in the Arabian Sea for the last 6000 years based on paleobiological records in sediments from the continental margin of Pakistan at two levels of ecological complexity: sedimentary ancient DNA reflecting water column environmental states and planktonic foraminifers sensitive to winter conditions. We show that strong winter monsoons between ca. 4500 and 3000 years ago occurred during a period characterized by a series of weak interhemispheric temperature contrast intervals, which we identify as the early neoglacial anomalies (ENA). The strong winter monsoons during ENA were accompanied by changes in wind and precipitation patterns that are particularly evident across the eastern Northern Hemisphere and tropics. This coordinated climate reorganization may have helped trigger the metamorphosis of the urban Harappan civilization into a rural society through a push–pull migration from summer flood-deficient river valleys to the Himalayan piedmont plains with augmented winter rains. The decline in the winter monsoon between 3300 and 3000 years ago at the end of ENA could have played a role in the demise of the rural late Harappans during that time as the first Iron Age culture established itself on the Ghaggar-Hakra interfluve. Finally, we speculate that time-transgressive land cover changes due to aridification of the tropics may have led to a generalized instability of the global climate during ENA at the transition from the warmer Holocene thermal maximum to the cooler Neoglacial.